Integrating data to redescribe Euschistus taurulus Berg (Hemiptera: Pentatomidae) - Hickmann, Frederico; Moraes, Tamara; Bianchi, Filipe Michels; Corrêa, Alberto Soares; Schwertner, Cristiano Feldens (Zootaxa, 2019)
The genus Euschistus Dallas includes 67 species restricted to the New World, and several species are registered on cultivated plants in the Nearctic and Neotropical regions. In South America, most Euschistus species are completely overlooked due to the lack of information to allow accurate identification. Here, we redescribed Euschistus taurulus Berg, including for the first time, characterization of the internal and external genitalia of both sexes. We also report original information on bionomics, review and update information on geographical distribution and host plants records. Additionally, we provide DNA barcoding sequences for E. taurulus and three other morphologically similar key-agriculture pest species in South America: Euschistus heros (Fabricius), Dichelops melacanthus (Dallas), and Dichelops furcatus (Fabricius). We discuss means for correct identification of E. taurulus and its phylogenetic position within Euschistus and other similar stink bugs; the potential economic importance of the E. taurulus is also addressed.